2007
DOI: 10.1111/j.1365-246x.2006.03246.x
|View full text |Cite
|
Sign up to set email alerts
|

Land subsidence in Mashhad Valley, northeast Iran: results from InSAR, levelling and GPS

Abstract: SUMMARY Significant land subsidence was recently recognized in northeast Iran, near the city of Mashhad. Precise levelling surveys performed in 1995, 2002 and 2005, indicate as much as 90 cm of subsidence during the 1995–2005 period. Continuous GPS monitoring approximately 8 km northwest of Mashhad City shows more than 20 cm yr−1 subsidence between 2005 and 2006. We use Interferometric Synthetic Aperture Radar (InSAR) measurements to detect the temporal and spatial pattern of this surface deformation. 13 inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
68
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(72 citation statements)
references
References 32 publications
3
68
0
1
Order By: Relevance
“…Land subsidence is a major environmental problem in some countries as it can cause serious damages to the urban components such as: structures, buildings and sanitary sewers as a long-term deformation (Motagh et al 2007;Dehghani et al 2009;Osmanoglu et al 2011;Lubis et al 2011;Rigo et al 2013). It may occur due to various reasons such as & Sadra Karimzadeh sadra.karimzadeh@gmail.com; s.karimzadeh@stu.kanazawa-u.ac.jp earthquakes, mining, over extraction of oil, natural gas or groundwater and some urban activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Land subsidence is a major environmental problem in some countries as it can cause serious damages to the urban components such as: structures, buildings and sanitary sewers as a long-term deformation (Motagh et al 2007;Dehghani et al 2009;Osmanoglu et al 2011;Lubis et al 2011;Rigo et al 2013). It may occur due to various reasons such as & Sadra Karimzadeh sadra.karimzadeh@gmail.com; s.karimzadeh@stu.kanazawa-u.ac.jp earthquakes, mining, over extraction of oil, natural gas or groundwater and some urban activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Central basin as the biggest basin in term of land area has less than one third of the renewable water resources (FAO 2009). Excessive water (or other fluids) withdrawals have caused land subsidence throughout the country (Alipour et al 2008;Anderssohn et al 2008;Dehghani et al 2009;Motagh et al 2007) due to pore fluid pressure decreasing between granules in unconsolidated sediments (weak materials) (Hoffmann and Zebker 2001;Bell et al 2008). Balance of downfall and water extraction could be helpful to control or mitigate the probable hazards in the future (Motagh et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[4] Surface deformation attributed to hydrogeologic processes in groundwater basins has been successfully observed by Interferometric Synthetic Aperture Radar (InSAR) and Global Positioning System (GPS) [e.g., Bawden et al, 2001;Watson et al, 2002;Lanari et al, 2004;Argus et al, 2005;King et al, 2007;Motagh et al, 2007]. Using both techniques, King et al [2007] reported an expansion ($10 mm) and uplift ($47 mm) of the San Gabriel Valley aquifers recharged after near-record rainfall ($95 cm on downtown Los Angeles which is 2.5 times larger than the seasonal average of 38 cm [King et al, 2007] Based on the history of abrupt water level increases at a nearby well, King et al [2007] predicted that other signals caused by large amount of groundwater recharge are likely to occur in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The destruction of bridges, roads, structures and municipal facilities and etc., are some of the damages which are caused by land International Research Conference on Civil, Architectural and Environmental Engineering (IRCCAEE) Istanbul (Turkey) May. [17][18]2017 subsidence (Poland and Davis, 1969;Amighpey et al, 2006;Mahmoudpour et al, 2013;Motagh, et al, 2007Motagh, et al, , 2008; Bell et al, 2002;Ortiz-Zamora, et al, 2010). The consensus among experts and environment officials is that Tehran, capital of Iran and around it is losing the battle against land subsidence.…”
Section: Introductionmentioning
confidence: 99%